The affordances of rubrics in L2 writing in Higher Education: A new approach to enhancing writing conventions - Garcés-Manzanera, Aitor (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
The use of diverse techniques for the evaluation of writing tasks in English as a Foreign Language (EFL) has made its way into the EFL classroom in order to facilitate both the teachers’ task and the L2 students’ comprehension. Thus, the aim of this paper is to explore how undergraduate students may be trained in the use of rubrics, an ecologically valid feedback technique, and how they might assess sample writing tasks. This way, we will observe how able they are to identify dissimilarities and consistencies in these writing tasks on the basis of a specific genre as an article.